From Stage to Page: Adaptation as Survival in Neil Gaiman’s Mr. Punch. - Cox, Jennifer K. (Journal of the Fantastic in the Arts, 2019)
Neil Gaiman and Dave McKean perform a radical adaptation of both mythical form and magical content by translating the Punch and Judy showâ€™s lengthy folkloric tradition of puppetry into graphic novel format in The Tragical Comedy or Comical Tragedy of Mr. Punch (1994). This collaboration reframes archaic story elements with contemporary contexts to help adapt the mythical source material as well as readers themselves. In this way, the story form acts as a literary adapter, similar to a travel adapter for electronics: it allows readers to â€œplug inâ€ to access tales from distant cultures and historical eras. Filtering the puppet showâ€™s content through the narratorâ€™s childhood memories preserves a childlike perception of magic, but updates Punchâ€™s story with an added layer of adult understanding. This kind of storytelling, called a memorate, allows Gaimanâ€™s narrator to ventriloquize repressed traumas by retelling them as uncanny encounters with a murderous Mr. Punch.